The heart of the Buddha's teaching : transforming suffering into peace, joy & liberation : the four noble truths, the noble eightfold path, and other basic Buddhist teachings /: transforming suffering into peace, joy & liberation : the four noble truths, the noble eightfold path, and other basic Buddhist teachings. ([1999 1998]) - Unknown
No abstract available